Emotion, rationality, and decision-making: how to link affective and social neuroscience with social theory - Verweij, Marco; Senior, Timothy J.; Domínguez D., Juan F.; Turner, Robert (Frontiers in Neuroscience, 2015)
In this paper, we argue for a stronger engagement between concepts in affective and social neuroscience on the one hand, and theories from the fields of anthropology, economics, political science and sociology on the other. Affective and social neuroscience could provide an additional assessment of social theories. We argue that some of the most influential social theories of the last four decades –rational choice theory, behavioral economics, and post-structuralism– contain assumptions that are inconsistent with key findings in affective and social neuroscience. We also show that another approach from the social sciences –plural rationality theory– shows greater compatibility with these findings. We further claim that, in their turn, social theories can strengthen affective and social neuroscience. The former can provide more precise formulations of the social phenomena that neuroscientific models have targeted, can help neuroscientists who build these models become more aware of their social and cultural biases, and can even improve the models themselves. To illustrate, we show how plural rationality theory can be used to further specify and test the somatic marker hypothesis. Thus, we aim to accelerate the much-needed merger of social theories with affective and social neuroscience.